2023
DOI: 10.3390/jcm12227017
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Soft Tissues Healing after Lower Third Molar Extraction: Comparison of Two Different Access Flaps

Alessia Pardo,
Annarita Signoriello,
Martina Corrà
et al.

Abstract: Background: As specific flap designs performed for lower third molar extractions usually influence periodontal healing of the adjacent first and second molars, this study aimed to evaluate the periodontal conditions of these sites after 6 months post-surgery. Methods: Forty patients, aged 14–30 years, were included. Surgical extraction of the lower third molar was performed through a flap with papilla detachment (a modified envelope technique with detachment of gingival papilla between the first and second mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Flap design has assumed particular importance in recent years, especially for the extraction of impacted mandibular wisdom teeth. Attention has been paid to improving periodontal healing in the second molar and wound closure [ 25 , 26 , 27 , 28 ]. However, in these studies, no significant advantages were observed for postoperative pain or edema.…”
Section: Discussionmentioning
confidence: 99%
“…Flap design has assumed particular importance in recent years, especially for the extraction of impacted mandibular wisdom teeth. Attention has been paid to improving periodontal healing in the second molar and wound closure [ 25 , 26 , 27 , 28 ]. However, in these studies, no significant advantages were observed for postoperative pain or edema.…”
Section: Discussionmentioning
confidence: 99%